Welfare Costs of Crime and Common Violence: A Critical Review - Rodrigo Reis Soares
This paper critically reviews a vast array of literature on the costs of crime and common violence. Using a simple economic model of crime as a theoretical benchmark, we conceptually discuss the estimates available and their potential use as inputs for public policy. We present current methodologies, explore their main results, discuss their limitations, and suggest directions for further research.crime, violence, welfare, costs, contingent valuation, willingness to pay JEL codes: K42, O17, O57